PERIBULBAR ANESTHESIA WITH TARGETED INTRAVENOUS ESKETAMINE ANALGOSEDATION DURING ENUCLEATION: A CONTEMPORARY NARRATIVE REVIEW: ESKETAMINE-GUIDED ANALGOSEDATION DURING ENUCLEATION - Lučić, Margita; Vasović, Dolika (Srpski medicinski časopis Lekarske komore, 2026)
Introduction: Enucleation is an invasive ophthalmic procedure accompanied by pronounced nociceptive and reflex stimuli, representing a significant anesthesiological challenge, particularly in elderly and comorbid patients. Contemporary anesthesiology trends increasingly favor the use of regional anesthesia combined with targeted analgosedation as a safer alternative to general anesthesia.Aim: To present current concepts of peribulbar anesthesia combined with targeted intravenous esketamine-guided analgosedation during enucleation, with special emphasis on hemodynamic stability, prevention of the oculocardiac reflex, control of perioperative pain, postoperative nausea and vomiting, and the feasibility of integrating this technique into day-surgery protocols.Methods: A narrative review of contemporary literature in the fields of ophthalmic and regional anesthesia was conducted, focusing on the pharmacological properties of esketamine, the mechanisms of action of the peribulbar block, and the clinical aspects of their combined use during enucleation.Conclusion: Peribulbar anesthesia combined with esketamine-guided targeted analgosedation represents a safe and effective contemporary anesthesiological approach for performing enucleation, particularly in elderly and comorbid patients. This approach provides stable hemodynamics, preserved spontaneous respiration, adequate pain control, a low incidence of postoperative nausea and vomiting, and rapid functional recovery, with the potential for application within a day-surgery setting.
Keywords: enucleation; peribulbar anesthesia; esketamine; analgosedation; oculocardiac reflex